Effect Of Building Shape On A Residential Building's Construction, Energy And Life Cycle Costs - BOSTANCIOĞLU, ESRA (Earthscan, 14A St Cross Street, London, Ec1N 8Xa, England, 2010)
When reducing the cost of residential buildings, decreasing operational costs along with the construction costs will prove beneficial not only for the owner and/or user of the residence but also for national economy. In the design phase, decisions regarding building shape have a considerable effect on both construction costs and building heating energy costs. Therefore, this study will analyse the extent to which changes in building shape affect construction costs and building heating energy costs, and thereby provide pre-design information for future reference for residential buildings with less energy consumption and less environmental pollution. To this end, residential buildings with the same characteristics have been used by differentiating only building shapes, orientations and envelope alternatives to assess the changes they cause in construction, energy and life cycle costs.
Keywords: Building Shape; Construction Cost; Energy Efficiency; Energy Cost; Envelope Design; Life Cycle Cost; Heat-Source Utilization; Functional Structure; Optimization; Design; Well; Yapı Şekli; İnşaat Maliyeti; Enerji Verimliliği; Enerji Maliyeti; Zarf Tasarımı; Yaşam Döngüsü Maliyeti; Isı Kaynak Kullanımı; Fonksiyonel Yapı; Optimizasyon; Dizayn